The emerging roles of GPR158 in the regulation of the endocrine system - Lin, Jinju; Li, Qin; Lei, Xiaohua; Zhao, Huashan (Frontiers in Cell and Developmental Biology, 2022)
G protein-coupled receptor 158 (GPR158) is a member of the class C G protein-coupled receptors (GPCRs), with high expression in the central nervous system (CNS) and low expression in peripheral tissues. Previous studies mainly focus on its functions in the CNS, such as regulating emotions, memory and cognition, whereas there have been few studies showing that GPR158 also play significant roles in the non-nervous system. Recently, it is reported that GPR158 is directly involved in the regulation of adrenal function, suggesting that the roles of GPR158 in peripheral tissues with low expression level. And the structure related to GPR158 has also been characterized, which is a stable dimer coupled to the regulator of G protein signaling protein 7 (RGS7) and forms the GPR158-RGS7-Gβ5 complex. Given the RGS7-Gβ5 complex is related to some endocrine functions, we speculate that GPR158 would be an active participant in endocrine system. Here, we review the relevant literatures on GPR158, including its molecular structure, regulatory molecules, expression and functions, and highlight the roles of GPR158 in endocrine regulation. These cues not only provide a novel comprehension on GPR158 from endocrine perspective, but also shed light on drug exploration targeting GPR158 and its application in endocrine disorders.